Assessment of aggregate resources: an integrated geophysical approach. Issue 6 (1st September 2013) - O'Driscoll, R.; Stuart, G.; Tuckwell, G.; Sergeant, J.
ABSTRACT: Fluvio‐glacial sand and gravel provide an important resource for the construction industry. The efficient and economic extraction of such geologically complex deposits requires a detailed understanding of their grade distribution. This is typically undertaken as point observations over the resource using a borehole drilling programme. We investigate the viability of using measurements of the elastic and electrical properties of the subsurface, derived from geophysical profiles, to determine the spatial variability of aggregate quality. A refraction seismic, surface wave seismic and resistivity survey was carried out over a fluvioglacial sand and gravel deposit at Scorton, Yorkshire, UK, on agricultural land adjacent to an active quarry. Two 190 m profiles, with borehole control at their extremes, were acquired with a 2 m source and receiver spacing. The P‐ and S‐wave velocities ( V p and V s ), together with resistivity and depth distributions were determined down to c. 20 m. The subsurface was divided into four layers: uncon‐solidated sand and gravel; dry consolidated sand and gravel; saturated sand and gravel; and basal clay. The work flow initially involved processing and interpreting the three geophysical techniques independently. Crossplots of the elastic and electrical parameters were used to distinguish unconsolidated from consolidated material; the water table; increased silt content; and recognize the basal clay. The Vp/Vs ratio proved very powerful at discriminating fine material ( V p /V s   ~   3 ) from coarse material (Vp/Vs ~ 1.5). Regression analysis of crossplots produced P‐ and S‐wave relationships for the material, while electro‐acoustic relationships were less successful, especially below the water table. The results of the petrophysical analysis were used to set up guided inversions for the resistivity survey. Careful use of the refraction results as an a priori model for the resistivity survey was found to improve the resistivity inversion, though use of a sharp boundary introduced edge effects at the water table. The results from the integrated analysis were combined with the guided inversions into a final interpretation that enabled silt content, particle size and clay lenses to be mapped, which were not identified in the separately processed data.